Things they lost : a novel - Oduor, Okwiri (Scribner, an imprint of Simon & Schuster, Inc., 2022)
"This astonishing, devastating debut novel, riven through with mystery and magic, tells the story of a lonely girl living in a small African town and her struggle to free herself from her mercurial, charming mother. Ayosa is a wandering spirit- joyous, exuberant, filled to the brim with longing. Her only companions in her grandmother's crumbling house are as lonely as Ayosa herself: the ghostly Fatumas, whose eyes are the size of bay windows, who teach her to dance and wail at the death news; the Jolly-Annas, cruel birds who cover their solitude with spiteful laughter; the milkman, who never greets Ayosa and whose milk tastes of mud; and Sindano, the kind owner of a café no one ever visits. Unexpectedly, miraculously, one day Ayosa finds a friend. Yet she is always fixed on her beautiful mama, Nabumbo Promise: a mysterious and aloof photographer, she comes and goes as she pleases, with no apology or warning. Set at the intersection of the spirit world and the human one. "Things They Lost" is a stunning and unforgettable novel that unfurls the dizzying dualities of love, at its most intoxicating and all-encompassing."--